Cost Minimization Analysis of Antibiotic Drug Use in Pneumonia Patients at Udayana Class II Hospital - Luh Santhi Utami Wiryani; Fitria Megawati; I Dewa Agung Ayu Diva Candraningrat (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Pneumonia is one of the leading causes of morbidity and mortality in Indonesia, with a high economic burden mainly due to antibiotic use, which consumes a large portion of hospital budgets. This study aimed to analyze the cost-minimization of antibiotic therapy in hospitalized pneumonia patients at Tk II Udayana Hospital. A descriptive non-experimental retrospective study was conducted using medical records of pneumonia inpatients at Tk.II Udayana Hospital from January to December 2023. A total of 138 patients met the inclusion criteria. Data analyzed included demographics, length of stay, and direct medical costs. Cost minimization analysis was performed by comparing the average direct medical costs of each antibiotic therapy. Of 233 medical records screened, only 138 fulfilled the criteria. Male patients (53.6%) were slightly more than females (46.4%), with the majority aged 1–5 years (64.5%). Most patients had a length of stay of 1–7 days (99.3%). Antibiotics used included Ceftriaxone, Cefotaxime, Azithromycin, Cefoperazone, and Cefixime (monotherapy or combination). The highest direct medical cost was found in Ceftriaxone monotherapy (IDR 1,973,061 ± 393,521), while the lowest was in Cefixime monotherapy (IDR 1,574,659 ± 39,208). Statistical analysis using the Mann-Whitney test showed no significant difference in costs based on the length of stay (p=0.123). Cefixime monotherapy was the most cost-minimization therapy for pneumonia inpatients at Tk.II Udayana Hospital, with equal clinical effectiveness but lower costs compared to other therapies. This finding may serve as a consideration for hospital formulary development to improve budget efficiency without compromising quality of care.